Com licença Hip-hop : mapeamento dos grupos de Hip-hop na Grande Vitória, Espírito Santo - Amaral, Elizabeth de Souza (2009)
This dissertation aimed to draw a map of the Hip-hop groups in Grande Vitória / Espírito Santo. The names of the participants in this study were kept as a methodological resource to facilitate the narration of stories of the characters who make the Hip-hop. The analysis reported here were made from the concept of power, resistance and biopower in Foucault. It was also presented the crossover of some conceptions collected in Deleuze, Guattari, Rolnik, Benevides. It was discussed the social movements made in Brazil in the 1970s and 1980s and highlighted the emergence of social movements, such as Hip-hop at the end of the '80s, as a different form of expression of collective actions and the emergence of other ways of living in society, indicating the actions of resistance and the clash of forces experienced in the biopower. It was presented, about the Hip-hop, an overview of its history in the world, in Brazil and in Grande Vitória, Espírito Santo. Because it is a group composed of a majority of young people, some highlights about the youth in Brazil and in the State of Espírito Santo were brought up, in order to denaturalize the youth as nature and stage of life. Methodologically, the interviews and the lyrics of the songs were taken to trace the analyzer thematics that put in question the practices and processes that make the Hip-hop in Grande Vitória, Espírito Santo.